2023
DOI: 10.1177/08862605221145721
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Subjective Well-Being Among Chinese Adolescents: Moderated Mediation by Forgiveness and Self-Esteem

Abstract: Considerable developmental research has shown an association between peer victimization and subjective well-being among adolescents. However, the mediating processes and protective factors that constrain this association are less understood. To fill these gaps, we investigated whether self-esteem mediates the association between peer victimization and subjective well-being and whether forgiveness moderates the direct and indirect associations of peer victimization with adolescents’ subjective well-being via se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…The scientific literature exposes the existing problem with school violence and the consequences that this problem has on young people [1,6,8]. Most previous research focuses on identifying existing relationships with other variables in school violence roles focused on being a victim or being an aggressor [12][13][14][15][16]22,23]. These studies are scarcer when it comes to research on young people who are bystanders or non-bystanders of school violence, so this research wanted to inquire about this role that also exists and can affect adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific literature exposes the existing problem with school violence and the consequences that this problem has on young people [1,6,8]. Most previous research focuses on identifying existing relationships with other variables in school violence roles focused on being a victim or being an aggressor [12][13][14][15][16]22,23]. These studies are scarcer when it comes to research on young people who are bystanders or non-bystanders of school violence, so this research wanted to inquire about this role that also exists and can affect adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…One particular study, conducted by Wu et al [22], highlights that the mental health consequences derived from bullying vary according to the role in the situation, being more pronounced in victims and bystanders than in the bullies themselves. Recent research showed that adolescents who are participants in school violence experience a deterioration in their self-esteem and present a decrease in their coping skills [23]. This phenomenon can negatively affect their self-perception and their ability to cope with future challenges [24].…”
Section: Introductionmentioning
confidence: 99%
“…Related research findings showed that reciprocal positive relationships between parental support and self-esteem (Yuan et al, 2023). low selfesteem was associated with decreased subjective well-being (Liu et al, 2023), and self-esteem partially mediated the link between emotional intelligence and creative self-efficacy (Chen and Cheng, 2023). It can be seen that Chinese scholars used to describe the self-esteem status of adolescents from the micro perspective, and the comprehensive analysis of adolescent self-esteem from the macro perspective can enrich the results of self-esteem research in China.…”
Section: Research Status Of Self-esteem In Chinese Adolescentsmentioning
confidence: 99%
“…Wu Xiqing, Hu Qian, and Chen Cui et al found that there is a significant negative correlation between trait anger and forgiveness, and the higher the level of forgiveness, the better the individual's ability to regulate anger [34]. Therefore, it is possible to cultivate one's ability to forgive, thereby reducing aggressive behaviors due to anger in life.Forgiveness levels moderated the direct effect of trait anger on cyberattack behavior in college students [21], which further explains that the emotion of anger influences the development of an individual's ability to forgive.Therefore, enhancing the level of forgiveness in individuals with high trait anger is important for controlling individual anger as well as avoiding problematic behaviors due to anger [35].…”
Section: Forgiveness Interventionmentioning
confidence: 99%